Measurement of Neutral Atmosphere Density during the Years of Increasing Solar Activity Using Insight-HXMT Data with the Earth Occultation Technique - Zhang, Hao-Hui; Xue, Wang-Chen; Li, Xiao-Bo; Zhang, Shuang-Nan; Xiong, Shao-Lin; Chen, Yong; Li, Hai-Tao; Song, Li-Ming; Ge, Ming-Yu; Zhao, Hai-Sheng; Yu, Yun-Wei (The Astrophysical journal, 2025)
The density of the Earth’s middle and upper atmosphere is an important parameter in Earth science and plays a critical role in the design, operation, and orbital determination of low Earth orbit spacecraft. In this study, we have employed the Earth occultation technique combined with maximum likelihood estimation to estimate the neutral atmospheric density by modeling the attenuation of X-ray photons during the occultation process of Insight-HXMT observations of Crab Nebula. By comparing with blank sky occultation data, we demonstrate that the contribution from cosmic X-ray background can be negligible, which has allowed us to extended our density inversion up to 130 km altitude. This is a significant improvement over earlier work. Based on 83 occultation data sets of the Crab Nebula observed by all three sets of telescopes of Insight-HXMT between 2022 and 2024, we derived the atmospheric densities at altitudes spanning from 55 to 130 km. The results show a general agreement between our results and the predictions from the Navy Research Laboratory Mass Spectrometer Incoherent Scatter Radar Exosphere (NRLMSIS) model within the altitude ranges of 65–90, 95–100, and 120–130 km, particularly during periods of increased solar activity. These retrieved atmospheric density results between 65 and 90 km are consistent with prior studies. However, we also find that the NRLMSIS model overestimates atmospheric density at altitudes 90–95 and 100–120 km by 15%–20%. Furthermore, since the atmospheric density measurements at altitudes of 55–65 km may be subject to selection bias, we do not report the prediction accuracy of the NRLMSIS model at this altitude.